Increasing Drug Abuse Education Among Adolescents at the MTs and MA Levels - Putri, Devita Rahma; Ratna, Noviantika (UNUSA Press, 2023)
The problem of drugs in Indonesia is still urgent and complex. Drug abuse is included in one of the special forms of juvenile delinquency. The purpose of this study was to reduce the prevalence of drug abuse among adolescents by counseling MTs and MA students. The research method used a multistage random sampling method, namely giving a pre-test and post-test at the time of counseling. The population in this study were MTs and MA students in Randegansari Village with a total of 140 people. The results showed that before drug counseling, almost all MTs and MA students had a low level of knowledge, namely 95 people (67.86%). However, after counseling related to basic knowledge, dangers, impacts and threats of criminal law of drug acts, almost all students increased their knowledge level, namely 108 people (77.14%). The conclusion shows that students' knowledge of drugs is influenced by the surrounding environment such as the family environment, school environment, and the community environment where adolescents actualize themselves. Suggestions in overcoming drug abuse require efforts and support from all parties to achieve the expected goals. Prevention and control of drugs can still be done to prevent use and help adolescents who have fallen into drug abuse.